Single-Appointment Fabrication of Interim Immediate Denture: A Clinical Report - Memari, Yeganeh; Gooya, Ali (Journal of Dental School, 2020)
Objective: An immediate complete denture is fabricated before the extraction of all teeth. It has several advantages such as preservation of esthetics, muscular tone, normal speech and reduction of post-operative pain. This report describes a method of using patient’s current fixed partial denture (FPD) for single-appointment construction of interim immediate denture. Case: We used patient’s existing maxillary FPD for single-appointment fabrication of an interim immediate denture; which was delivered to the patient after the extraction of his remaining maxillary teeth. Conclusion: Within a short time, an interim immediate denture can be fabricated for patients to preserve occlusion, vertical facial height and facial appearance until the fabrication of final prosthesis.